Elevated KIAA0101 expression is a marker of recurrence in human gastric cancer. Issue 3 (18th February 2013) - Zhu, Kun; Diao, Dongmei; Dang, Chengxue; Shi, Lei; Wang, Jianguang; Yan, Rong; Yuan, Dawei; Li, Kang
<x xml:space="preserve">Abstract</x> Gastric cancer (GC) is one of the most common malignant tumors with a high rate of recurrence, which results in surgery being unsuccessful. Therefore, it is important to find the reason for the surgery failing. The purpose of the present study was to investigate a factor related to recurrence. Expression of KIAA0101 was assessed in 61 paired human primary GC and non‐cancerous gastric tissue using immunohistochemistry. After surgery, all 61 patients were followed regularly for more than 24 months or until death to analyze the 2‐year survival rate and recurrence. After suppressing KIAA0101 by RNA interference in human GC cell lines, the cell viability was detected using MTT. We are first to find that KIAA0101 was elevated in GC tissues compared with paired non‐cancerous gastric tissues. Immunohistochemical staining also revealed the predominant nuclear localization of KIAA0101 protein. Despite these findings, GC patients with elevated KIAA0101 expression levels exhibited a high recurrence and subsequently poor prognosis in the survival study. Also, cell viability was significantly inhibited after suppressing KIAA0101 in GC cells, suggesting that KIAA0101 might promote cancer cell proliferation. KIAA0101 is increased in human GC and is a marker of recurrence.